(untitled) (International Journal of Engineering and Computer Science, 2018)
Nowadays, Mobile devices like cellular phones are widely used by most people. This rapid growth in mobile technology makes the delivery of healthcare data on mobile phones. The healthcare data is very sensitive and hence, it must be protected against unauthorized access. Mobile device have two constraints: Memory and Processing Power. AES is well-known standard algorithm for encryption. AES is a block cipher.AES provides flexibility, simplicity, easiness of implementation and high throughput.